Influences of Antecendent and Outcome Factors on The Speed of New Product Development: A Study of SME Companies in Indonesia - Kurnia, Pepey Riawati (UI Scholars Hub, 2021)
The research’s objective is doing an empirical test toward research conducted by Menon & Lukas (2004), which generates 6 propositions of antecedent and outcome factors in the velocity of new product development. The literature theory based on theory of new product development speed (PDS) with antecendent and outcome factors. The research towards 63 respondent managers of Small and Medium Enterprises (SME) companies in Jabodetabek, Indonesia. Six propositions are developed into 6 hypotheses, which are then subject to a statistical test using LVS. Goodness-of-fit test informs that 6 hypotheses are eligible and so does the Measurement-fit test. Test towards 6 hypotheses using significance level of 0.05 with t value of > 1.96 confirms that the data support 5 hypotheses, except for hypothesis number 6 which states that Product Development Speed has no influence on the Orga- nizational Stress. The results provide managerial, theoretical insight and implication that are useful for New Product Development Speed.